Was John the Baptist Raised from the Dead? - Vette, Nathanael; Robinson, Will (The Biblical Annals, 2019)
In the vox populi of Mark 6:14-16 (cf. 8:28), we find the puzzling claim that some believed Jesus was John the Baptist raised from the dead. The presentation of John in the Gospel is similar to Jesus: Mark depicts John as a prophetic figure who is arrested, executed, buried by his disciples, and—according to some—raised from the dead. This paper reviews scholarship on the question of whether the tradition concerning John's resurrection—as well as the tradition concerning his death to which it is prefixed (6:17-29)—originated outside of the early Christian community. We examine the possibility that sects or individuals in the ancient world believed John had indeed been raised from the dead—as well as figures supposedly connected to John (Dositheus, Simon Magus). We conclude on the basis of internal evidence from the Gospel that the report in 6:14-16 likely originated in a Christian context. At the same time, it may also provide a glimpse into first-century CE attitudes concerning the resurrection from the dead.